PERBEDAAN JENIS MULSA DAN VARIETAS TERHADAP PERTUMBUHAN DAN HASIL JAGUNG MANIS (Zea mays saccharata Sturt.) - Retna Candra Yuwana, Alfia; Jumadi, Rahmad; Sri Redjeki, Endah (Politeknik Negeri Ketapang, 2023)
Production of sweet corn in Indonesia has decreased accompanied by increased consumer demand, the reason being the lack of availability of superior seeds and weed disturbances. The use of mulch and varieties can increase crop production. This study aims to determine the growth and yield of sweet corn with different types of mulch and varieties. This study used a randomized block design with two factors, the first factor was the type of mulch (M) and the second factor was the variety (V). M0 : without mulch, M1 : rice straw mulch, M2 : silver black plastic mulch, V1 : Master Sweet, V2 : Bonanza, M3 : Sweet Boy. These factors were combined into 9 treatments and repeated 3 times resulting in 27 experimental units. Data analysis used a 5% significant level of variance and then tested further with Duncan's Multiple Range Test at a 5% significant level and correlation test. The results showed that there were significant differences in the interaction between mulch types and varieties on stem diameter at 4, 6, and 8 weeks after planting. Fresh weight of cobs without corn kernels per plant, estimated per plot and per hectare. Meanwhile, the variables of plant height, number of leaves, cob length, cob diameter, number of seed rows, and brix showed no significant interaction.